Investigation of factors that affect post-fire recovery of photosynthetic activity at global scale - Yicheng Shen; I. Colin Prentice; Sandy P. Harrison (Ecological Indicators)
The time taken for ecosystems to recover after wildfire affects the rate of carbon sequestration, and this in turn impacts land–atmosphere exchanges and hydrological processes. Factors affecting post-fire recovery time have been investigated at site or regional scale, but there is comparatively little information about this at a global scale. In this study, we use solar-induced chlorophyll fluorescence (SIF) to estimate the recovery of photosynthetic activity after fire for more than 10,000 fires representing the range of ecosystems across the globe. We then examined the factors that influence post-fire recovery time, initially using the relaxed lasso technique to identify the most important factors and then using a linear regression model incorporating these factors. We show that vegetation characteristics, the characteristics of the fire, and post-fire climate all influence recovery time. Gross primary production (GPP) is the most important factor, with faster recovery in ecosystems with higher GPP. Fire properties which indicate substantial vegetation damage, such as fire intensity and duration, result in longer recovery times. Post-fire climate also affects recovery time: anomalous temperature and temperature seasonality, and higher than normal dry days increase recovery time while higher-than-average precipitation decreases recovery time. There is an additional impact of vegetation type (biome), which may reflect differences in plant adaptations to fire between biomes. We show that there is a clear relationship between the proportion of plants that resprout after fire in a biome and recovery time, with ecosystems characterised by higher abundance recovering faster.